2008
DOI: 10.1002/nml.214
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic charitable giving: An opportunity for nonprofit development

Abstract: In 2003, the U.S. Census Bureau indicated that Hispanics had become the largest U.S. minority group. Representing 14 percent of the population, more than forty million Hispanics currently live in the United States and are a growing source of charitable giving. This study uses a national probability sample (n = 3,261) to examine variables that may influence Hispanic charitable giving in the United States to private nonprofit organizations. Logistic regression analyses indicated that Hispanics were eight times m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In a 2008 study of 224 Hispanic Americans, Marx and Carter found that Hispanic donors who used payroll deduction were eight times as likely to give to human services, than Hispanic givers who did not use payroll deduction [11]. In addition, Hispanic givers who volunteered their time were twice as likely to donate to youth development as Hispanic donors who did not volunteer.…”
Section: Past Researchmentioning
confidence: 99%
“…In a 2008 study of 224 Hispanic Americans, Marx and Carter found that Hispanic donors who used payroll deduction were eight times as likely to give to human services, than Hispanic givers who did not use payroll deduction [11]. In addition, Hispanic givers who volunteered their time were twice as likely to donate to youth development as Hispanic donors who did not volunteer.…”
Section: Past Researchmentioning
confidence: 99%
“…The most popular organizations in which Latina/os volunteer are religious organizations 19%, education field 17%, youth organizations 13%, such as the Boys and Girls Club, and informal activities 12%, such as baking for school fundraisers, helping friends, or free childcare (Diaz et al, 2001). Similarly, Marx and Carter (2008) found community organizations benefit monetarily from Latina/os through philanthropic activities, such as fundraising. It will be interesting to see how and where…”
Section: Volunteeringmentioning
confidence: 99%
“…of the total contributions made by Latinas/os are made to religious organizations (Diaz, et al, 2001). Stemming from the 1600s and 1700s in Latin America, the Roman Catholic Church has had a history of furnishing financial, legal, and social services, especially for needy families (Marx & Carter, 2008 were established to provide advocacy on behalf of the Latina/o community in the areas of employment, education, immigrant rights, and political access (Carson, 1999;Center of Philanthropy and Civil Society, 2003;Cortés, 1995;B. Smith, et al, 1999).…”
Section: Latina/o Participation With the Churchmentioning
confidence: 99%
“…Religion also plays an important role in Latina/o philanthropy. As indicated in Chapter 2, many Latinas/os rely on the church to provide most of their social needs, particularly for needy families (Marx & Carter, 2008;Ramos, 1999). The majority of the Latina/o alumni in this study participated in different types of church activities throughout their lives.…”
Section: Latina/o Philanthropymentioning
confidence: 99%
See 1 more Smart Citation